Assessment of reproducibility and reliability of facial expressions using 3D handheld scanner. Issue 6 (June 2019) - Özsoy, Umut; Sekerci, Rahime; Hizay, Arzu; Yildirim, Yilmaz; Uysal, Hilmi
Abstract: Purpose: The three-dimensional morphological analysis of facial expressions has been becoming increasingly common and hand-held three-dimensional scanners can be advantageous in data acquisition due to their mobility. The aim of the present study was to test intra-subject, intra-observer and inter-observer reproducibility and reliability of a hand-held scanner during facial expressions. Materials and methods: In order to investigate intra-subject reproducibility and reliability, we performed face scanning two times on 30 healthy subjects at three-month intervals. In addition, two observers scanned twice the face of 10 healthy subjects consecutively to evaluate intra-observer and inter-observer differences. Scannings were performed during facial expressions. Face asymmetry and severity of facial expression were determined using root mean square (RMS) value. Repeated-measurement ANOVA was used to test the reproducibility and correlation coefficient to determine the reliability of the facial expressions. Results: The mean RMS values measured at different times were not significantly different for any facial expression (p > 0.05). The reliability of the measurements was variable depending on the facial expression (r = 0.47 and 0.98, p < 0.05). Conclusions: Our study may contribute to the development of new techniques for examining facial expressions. Hereby, morphological analysis may be possible in the clinic and at the bedside without the need for laboratory conditions.